2011
DOI: 10.3349/ymj.2011.52.2.257
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Response of Amylin Levels after an Oral Glucose Challenge in Children with Prader-Willi Syndrome

Abstract: PurposeAmylin secretion is increased parallel to insulin in obese subjects. Despite their marked obesity, a state of relative hypoinsulinemia occurs in children with Prader-Willi syndrome (PWS). Based on the hypothesis that amylin levels may be relatively low in PWS children, contributing to their excessive appetite, we studied amylin levels after oral glucose loading in children with PWS and overweight controls.Materials and MethodsPlasma levels of amylin, glucagon, insulin, and glucose were measured at 0, 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Amylin Secretion in the Obese State. Although regulation of amylin secretion has not been extensively evaluated in humans, there is some evidence for elevation of amylin in the obese state (Ludvik et al, 1991;Enoki et al, 1992;Hanabusa et al, 1992; Amylin Blackard et al, 1994;Kautzky-Willer et al, 1994;Roth et al, 2010;Lee et al, 2011;Jacobsen et al, 2012). Plasma levels appear to reach up to approximately twice those achieved in nonobese subjects, but whether this results overall in sustained levels of amylin in excess of those that would be achieved postprandially is not clear.…”
Section: B Obesitymentioning
confidence: 99%
“…Amylin Secretion in the Obese State. Although regulation of amylin secretion has not been extensively evaluated in humans, there is some evidence for elevation of amylin in the obese state (Ludvik et al, 1991;Enoki et al, 1992;Hanabusa et al, 1992; Amylin Blackard et al, 1994;Kautzky-Willer et al, 1994;Roth et al, 2010;Lee et al, 2011;Jacobsen et al, 2012). Plasma levels appear to reach up to approximately twice those achieved in nonobese subjects, but whether this results overall in sustained levels of amylin in excess of those that would be achieved postprandially is not clear.…”
Section: B Obesitymentioning
confidence: 99%
“…However, since the lack of BDNF postprandial peak was also shown in obese patients [ 22 ], BDNF postprandial peak in healthy subjects may have been masked by the lack of peak in obese (both in Cluster 1) and contributed to the absence of differences between clusters. There is only one study [ 20 ] evaluating amylin in children with PWS finding lower postprandial amylin concentrations which correlated with insulin concentrations. A relative hypoinsulinemia is described in PWS [ 16 , 17 , 44 ], and fasting insulin levels in PWS in the present study were in the same line, however, no differences between clusters were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies also agree finding low concentrations of pancreatic polypeptide (PP) [ 7 , 8 , 9 ]. The results are controversial with regard to other hormones such as peptide YY (PYY) [ 10 , 11 , 12 , 13 , 14 , 15 ] or Glucagon-like peptide-1 (GLP-1) [ 16 , 17 , 18 , 19 ], and there are few studies exploring others such as glucose-dependent insulinotropic polypeptide (GIP) [ 8 , 15 ], amylin [ 20 ] or brain-derived neurotrophic factor (BDNF) [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, circulating amylin levels seem to tightly correlate with fat mass. Studies indicate that basal and glucose or meal-stimulated levels of amylin are elevated in individuals with obesity (65)(66)(67)(68)(69)(70)(71)(72)(73)(74). This may relate to the role of amylin as a regulator of body mass but could also be a manifestation of the increased beta cell secretory activity often found in obesity.…”
Section: The Role Of Amylin In Obesitymentioning
confidence: 99%